EVALUATION OF SYMPTOMS OF A PATIENT WITH BLADDER CANCER RECEIVING PALLIATIVE CARE: A CASE STUDY - Bruna Eloise Lenhani; Nen Nalu Alves das Mercês (Universidade Federal do Paraná, 2017)
This study aimed to assess the symptoms of a patient with bladder cancer receiving palliative care. It is a case study, undertaken in March - June 2015, in a hospital service in the South of Brazil, with one male participant, with bladder cancer, and the main caregiver (daughter) who was 47 years old. Data was taken from the paper care records, electronic medical records, and 12 nursing assessments, using the Edmonton Symptom Assessment System (ESAS). The predominant symptoms were: tiredness, sleepiness, reduction in appetite, depression, anxiety, and reduced self-esteem. The study suggests that the symptoms - when not controlled - are directly related to lower quality of death; the importance was observed of using a specific scale for assessing the symptoms of patients receiving palliative care, in order to improve the care provided.